Effort Improving Learning Outcomes Mathematics On Matter Dimensions Three With Method Invention Supervised Participants _ educate Class XII IPA 1 SMAN 1 Rambah Academic Year 2022/2023 - Arisman Arisman; Fitri Fitri (STKIP Rokania Pasir Pangaraian, 2023)
This chamber of darjah action study contains 4 stages, namely planning, implementing the action, observing, and reflecting. The subjects in this study were 27 students of class XII IPA 1 at SMAN 1 Rambah consisting of 8 males and 19 females who had heterogeneous levels of proficiency. This research activity is carried out in two cycles, namely cycle I and cycle II. Prior to this, pre-circulation actions have been carried out to find out the implementation of learning that does not use the guided discovery method. The results of the study prove that the use of guided discovery methods can improve student learning activities and outcomes in three-dimensional materials.).